2022
DOI: 10.1093/milmed/usac143
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Associated With Intensive Care and Organ Support Among Patients With COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background Accurate accounting of coronavirus disease 2019 (COVID-19) critical care outcomes has important implications for health care delivery. Research Question We aimed to determine critical care and organ support outcomes of intensive care unit (ICU) COVID-19 patients and whether they varied depending on the completeness of study follow-up or admission time period. Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Our group previously reported a systematic review presenting data related to critical care outcomes in patients with COVID-19 (166). This review was limited by its inclusion of low-quality small sample studies and the restriction to studies published before the start of 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously reported a systematic review presenting data related to critical care outcomes in patients with COVID-19 (166). This review was limited by its inclusion of low-quality small sample studies and the restriction to studies published before the start of 2021.…”
Section: Discussionmentioning
confidence: 99%
“…38 The mortality rate from COVID-19 in our study population aligns with the reported rates in the literature, ranging from 25% to 55% for these patients. 41,42 Male sex, dyslipidemia, hyperkalemia, kidney injury, and orotracheal intubation were identified as factors related to mortality. Variables such as creatinine, bilirubin, PaCO 2 , and DEOx were independently associated with MODS, which are commonly associated with poorer outcomes in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies highlight the substantial impact of vaccination on the trajectory of the pandemic, with up to 90% protection against COVID-19-associated invasive mechanical ventilation (IMV) and death among adults (2,3). It is estimated that the mortality rate associated with IMV continues overcoming 30% (4). A recent systematic review and meta-analysis found a 43% (95% CI 0.29-0.58) pooled IMV mortality rate (1).…”
Section: Introductionmentioning
confidence: 99%
“…It predicts in-hospital mortality in patients with COVID-19 using easily accessible variables on admission: Age, BUN (blood urea nitrogen), Comorbidities, C-reactive protein, SpO 2 /FiO 2 ratio, Platelet count, and Heart rate. The score ranges from 0 to 20, with the following risk groups: low (0-1), intermediate (2)(3)(4), high (5)(6)(7)(8), and very high (≥9). It is freely available as an online risk calculator.…”
Section: Introductionmentioning
confidence: 99%